Childhood maltreatment, psychological resources, and depressive symptoms in women with breast cancer - Kuhlman, Kate Ryan (Child Abuse Negl, 2017)
Childhood maltreatment is associated with elevated risk for depression across the human lifespan. Identifying the pathways through which childhood maltreatment relates to depressive symptoms may elucidate intervention targets that have the potential to reduce the lifelong negative health sequelae of maltreatment exposure. In this cross-sectional study, 271 women with early-stage breast cancer were assessed after their diagnosis but before the start of adjuvant treatment (chemotherapy, radiation, endocrine therapy). Participants completed measures of childhood maltreatment exposure, psychological resources (optimism, mastery, self-esteem, mindfulness), and depressive symptoms. Using multiple mediation analyses, we examined which psychological resources uniquely mediated the relationship between childhood maltreatment and depressive symptoms. Exposure to maltreatment during childhood was robustly associated with lower psychological resources and elevated depressive symptoms. Further, lower optimism and mindfulness mediated the association between childhood maltreatment and elevated depressive symptoms. These results support existing theory that childhood maltreatment is associated with lower psychological resources, which partially explains elevated depressive symptoms in a sample of women facing breast cancer diagnosis and treatment. These findings warrant replication in populations facing other major life events and highlight the need for additional studies examining childhood maltreatment as a moderator of treatment outcomes.